A GSH-Responsive Nanoprodrug System Based on Self-Assembly of Lactose Modified Camptothecin for Targeted Drug Delivery and Combination Chemotherapy - Hou C (Dove Medical Press, 2020)
Chenxi Hou,1,* Ning Ma,1,* Ziyan Shen,1 Guanyu Chi,1 Shuang Chao,1 Yuxin Pei,1 Lan Chen,2 Yuchao Lu,2 Zhichao Pei1 1Shaanxi Key Laboratory of Natural Products & Chemical Biology, College of Chemistry and Pharmacy, Northwest A&F University, Yangling, Shaanxi 712100, People’s Republic of China; 2Analysis Center of College of Science & Technology, Hebei Agricultural University, Huanghua, Hebei 061100, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhichao Pei; Yuchao Lu Tel +86 29 87091196Fax +86 29 87092769Email peizc@nwafu.edu.cn; luyuchao@hebau.edu.cnBackground: Conventional chemotherapy using small molecular antitumor drugs suffers from several limitations, for instance poor water solubility, high toxicity, and lack of specificity. However, prodrugs constructed by covalent modification of anticancer drugs can overcome these limitations, which are able to release its active form after entering the tumor tissues by specific stimulus response.Methods: A GSH-responsive glyco-nanoprodrug system has been constructed by self-assembled of amphiphilic lactosemodified camptothecin prodrug molecular (Lac-SS-CPT) for targeting drug delivery and combination therapy.Results: Using HL7702 cells as experimental models, the cytotoxic effects of Lac-SS-CPT were investigated to 10– 30 μmol/L for 48 hours. Notably, the cell viability of Lac-SS-CPT to HL7702 cells was higher compared with free CPT which indicated that Lac-SS-CPT can reduce side-effects. Simultaneously, we have evaluated the anticancer efficiency of doxorubicin hydrochloride (DOX)-loaded Lac-SS-CPT glyco-nanoprodrug system (Lac-SS-CPT@DOX), where Lac-SS-CPT@DOX and free DOX incubated with HpeG2 cells and HL7702 cells for 24, 48, and 72 hours, respectively. It turned out that Lac-SS-CPT@DOX encapsulated anticancer drug (DOX) could decrease DOX side-effect on HL7702 cells and increase DOX anticancer efficiency. More importantly, the CPT and DOX were released from Lac-SS-CPT@DOX in HepG2 cells where a higher GSH concentration exists. Moreover, combination therapy efficiency was evaluated, where free DOX and Lac-SS-CPT@DOX incubated with DOX-resistance HepG2 cells (HepG2-ADR cells), respectively.Conclusion: The results revealed that the Lac-SS-CPT@DOX could enhance the cytotoxicity of DOX for HepG2-ADR cells and provided a new idea for designing an advanced nano-prodrug system toward combination therapy.Keywords: nanoprodrug, target, GSH-responsive, drug delivery, combination chemotherapy